2001
DOI: 10.2337/diabetes.50.6.1432
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Microthromboses in Retinal Capillaries of Diabetic Individuals

Abstract: In diabetic retinopathy, capillary nonperfusion and eventual obliteration can lead to retinal ischemia and sight-threatening neovascularization. The occurrence of retinal microthrombosis in human diabetes has long been suspected and occasionally observed but never systematically demonstrated. We used trypsin digestion to isolate the intact vascular network from retinas obtained postmortem from nine diabetic donors (age 64 ؎ 11 years, duration of diabetes 6 ؎ 4 years; mean ؎ SD) and eight age-matched nondiabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 37 publications
(37 reference statements)
2
77
0
1
Order By: Relevance
“…It has been reported that chronic hyperglycemia causes an increase in diacylglycerol (DAG) levels in the retina, which may activate PKC. 110 Through increased intracellular Ca 2ϩ , PKC stimulates endothelial cells, leuckocytes and platelets to produce platelet-activating factor (PAF). [111][112][113] PAF, confined to membranes, stimulates PAF receptors 114 on platelets, inducing activation of these platelets.…”
Section: Platelet Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that chronic hyperglycemia causes an increase in diacylglycerol (DAG) levels in the retina, which may activate PKC. 110 Through increased intracellular Ca 2ϩ , PKC stimulates endothelial cells, leuckocytes and platelets to produce platelet-activating factor (PAF). [111][112][113] PAF, confined to membranes, stimulates PAF receptors 114 on platelets, inducing activation of these platelets.…”
Section: Platelet Aggregationmentioning
confidence: 99%
“…122 Excess activation of endothelial PKC promotes PAF synthesis in diabetes. 110,123,124 PAF stimulates PAF receptors on peripheral leukocytes rolling on the lumenal endothelial membrane leading to their activation. 125 Activated leukocytes also synthesise PAF 126 and leukotriene B4 (LTB4), 127,128 which further enhance activation of leukocytes via autocrine action.…”
Section: Leukocyte Activation and Adherencementioning
confidence: 99%
“…In vitro, high FFA concentrations contribute to accelerated apoptosis of the endothelium (3-7), which ranks among the most endangered target tissues in diabetes. In diabetic retinopathy, endothelial apoptosis occurs before other histopathology is detectable (8), and procoagulatory apoptotic endothelial cells, topographically associated with microthromboses (9), could contribute to vascular occlusion. In atherosclerosis, in addition to its contribution to initial lesion formation owing to detachment of endothelial cells from the underlying intimal layer, endothelial apoptosis leads to increased vascular permeability, plaque erosion, and plaque rupture (10,11).…”
mentioning
confidence: 99%
“…Endothelial dysfunction plays a key role in the development of diabetic angiopathy (13,14), which is characterized by the increased turnover and exaggerated proliferation (neoangiogenesis) of the vascular endothelium and by procoagulant as well as proadhesive activity of apoptotic endothelial cells (15)(16)(17)(18).…”
mentioning
confidence: 99%